Aproximación a la regulación constitucional de la democracia participativa en Colombia y España. Estudio comparado. (2015)
With the constitutions of 1991 and 1978 as a benchmark, Colombia and Spain have respectively regulated various instruments of participatory democracy. This article aims to answer the research question of how to regulate constitutionally participatory democracy in both countries and defends the hypothesis that although the two countries have different regulations, with the Colombian much more developed than the Spanish, the practice in both countries is quite similar, is, low.